2020
DOI: 10.7759/cureus.7976
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Liver With Cardiac Compression Leading to Atrial Fibrillation: Case Report and Review of the Literature

Abstract: Polycystic liver disease (PCLD) is a rare condition that most often occurs in patients with polycystic kidney disease and less commonly as an isolated liver disease. Complications include cyst rupture, infection, hemorrhage, and compression of surrounding organs by large cysts. We present the case of a patient with a history of PCLD who presented to our hospital with palpitations and was found to have atrial fibrillation. Imaging and echocardiograph revealed a dominant large cyst compressing the right atrium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…While it is wellestablished that hypertension exacerbates ADPKD, 91 the impact of other cardiac alterations, such as AF, should also be considered. These observations raise the possibility that PKD1 mutations may have systemic effects, contributing to multi-organ dysfunction and potentially leading to conditions like AF 21,23,[27][28][29] , even in the absence of kidney disease and vice-versa. Therefore, the role of PKD1 mutations and their potential influence on AF progression warrant further investigation.…”
Section: Pc1-dependent Regulation Of Atrial Ec Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is wellestablished that hypertension exacerbates ADPKD, 91 the impact of other cardiac alterations, such as AF, should also be considered. These observations raise the possibility that PKD1 mutations may have systemic effects, contributing to multi-organ dysfunction and potentially leading to conditions like AF 21,23,[27][28][29] , even in the absence of kidney disease and vice-versa. Therefore, the role of PKD1 mutations and their potential influence on AF progression warrant further investigation.…”
Section: Pc1-dependent Regulation Of Atrial Ec Couplingmentioning
confidence: 99%
“…[22][23][24][25][26] Indeed, a recent study from the US-National Inpatient Sample database, including 71,531 patients, revealed that a higher risk of AF and atrial flutter was observed among ADPKD in the younger age group (18-39 years of age) compared to those with CKD and without ADPKD (odds ratio of 5.71). 27 Given that ADPKD increases the risk of AF 21,23,[27][28][29] , we investigated whether mutations in PC1 contribute to increased AF inducibility. PC1 is not only implicated in ADPKD but is also ubiquitously expressed across multiple tissues, including the heart, showing its broader biological significance.…”
Section: Introductionmentioning
confidence: 99%